Legal Analysis of The Obligation to use E-Government in Village Fund Management: A Case Study of Ketaon Village, Banyudono District, Boyolali Regency - Dody Dwi Kurniawan; Arief Budiono; Abdul Azis Manurung; Taufiq Hidayah (Proceeding International Conference Restructuring and Transforming Law, 2025)
Various aspects of life have become easier thanks to advances in information technology, including managing village government. E-government allows village fund management to be clearer and more efficient. The purpose of this study was to see how ready the technology infrastructure and digital literacy of Ketaon Village are to implement e-government in managing village funds. The method used is the empirical legal method using a qualitative and descriptive approach, observation, interviews, and document studies. The results of the study show that Ketaon Village faces many challenges when implementing e-government, including limited internet access, outdated hardware, and low digital literacy among village officials and the community. E-government has great potential to increase village transparency and accountability, this can speed up the administration process and facilitate the supervision of village funds.